Do Government Subsidies Induce Green Transition of Construction Industry? Evidence from Listed Firms in China - Feifei Zhang; Bingquan Liu; Guixin An (Buildings, 2024)
The construction industry is a major energy consumer and carbon emitter, and identifying the key drivers for its green transition has attracted increasing attention. Although government subsidies are one of the most effective and direct ways to induce a green transition, few academics have examined their effects at a micro level. Therefore, this study used the Chinese construction industry as an example to study the influence of subsidies on its green transition. Given the ambiguity of the green transition concept, this study employed the number of green patents and Environmental, Social, and Governance (ESG) ratings to represent the narrow sense and the wide sense of green transition, respectively. According to the empirical findings, subsidies can successfully induce green technology innovation and thus facilitate a green transition. The results of heterogeneity analysis show that government subsidies have a significant incentive-based effect solely on state-owned firms, but an insufficient effect on private and other enterprises. Furthermore, while government subsidies have little effect on ESG ratings, they can promote green transition of enterprises by increasing ESG ratings. The government should increase the types of subsidy packages available to enterprises, while attaching more importance to social responsibility.